(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, general concepts about the importance of ISO-9000 in the entry of industrial enterprises of Uzbekistan to the world market and the role of innovative technologies are briefly presented. In addition, attention is focused on the need to fill the domestic market with necessary consumer goods and deepen the level of localization by introducing international standards in the production of agricultural products, and it has been shown that it is time to pay great attention to increasing the volume of exports.